Republic of Armenia : First Review Under the Stand-By Arrangement, Request for Augmentation, Rephasing of Purchases, Waiver of the Nonobservance of Performance Criteria, and Modification of Performance Criteria; Staff Report, Press Release on the Executive Board Discussion, and Statement by the Executive Director for the Republic of Armenia. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses key findings of the First Review under the Stand-By Arrangement for the Republic of Armenia. In light of the large increase in Armenia's financing needs, the authorities have requested an augmentation of IMF resources in the amount of 180 percent of quota. The revised program maintains the original objectives of responding to the external outlook, strengthening confidence in the domestic currency and the banking sector, and protecting the poor, but would also allow an easing of monetary and fiscal policies to mitigate the severity of the crisis.